Seizure outcomes in children with Sturge-Weber syndrome undergoing epilepsy surgery: An individual participant data meta-analysis. (April 2023) - Mozaffari, Khashayar; Krishnakumar, Asha; Chen, Jia-Shu; Goel, Keshav; Wang, Andrew; Shlobin, Nathan A.; Weil, Alexander G.; Fallah, Aria
Highlights: Individual participant data meta-analysis of pediatric Sturge-Weber syndrome. Resective and hemispheric epilepsy surgery achieve comparable seizure outcomes. Resective surgery may be an appropriate alternative in some patients. Abstract: Background: A subpopulation of patients with Sturge-Weber syndrome (SWS) develop medically intractable epilepsy. There is a paucity of literature on preoperative factors that predict postoperative seizure outcomes in these patients. An individual participant data meta-analysis (IPDMA) was performed to discern preoperative variables associated with favorable seizure outcomes in pediatric SWS patients undergoing epilepsy surgery. Methods: PubMed, Cochrane, Web of Science, and Scopus were independently queried following PRISMA guidelines. Studies that reported seizure outcomes in individual pediatric SWS patients were selected. Preoperative demographic variables and disease characteristics were recorded and evaluated in a time-to-event fashion via Cox regression and Kaplan-Meier analysis with log-rank test. Results: A total of 18 studies with 108 patients were included for meta-analysis. Median age at seizure onset was 4.5 months, and 85 patients (78.7%) were seizure-free at last follow-up (median: 72 months). On multivariable Cox regression, no variables were independent predictors of post-operative seizure freedom duration, including the extent of hemispheric resection. There were also no differences in time-to-seizure recurrence on Kaplan-Meier analysis when comparing those treated with hemispheric surgery and those with less than hemispheric surgery ( p  = 0.52). Conclusion: This IPDMA showed that both resective and hemispheric epilepsy surgery achieve favorable and comparable seizure outcomes in pediatric SWS patients. The best available evidence using IPD suggests that resective surgery may be an appropriate alternative to hemispheric epilepsy surgery in well-selected patients. Prospective multi-institutional studies with greater follow-up are warranted to further investigate predictors of seizure outcome in pediatric SWS patients.